The persistence of violence : Colombian popular culture - Miller, Toby, 1958- (Rutgers University Press, 2020)
"Colombia's headline story, about the peace process with guerrilla and its attendant controversies, does not consider the fundamental contradiction of a nation that spans generosity and violence, warmth and hatred-products of its particular pattern of invasion, dispossession, and enslavement. The Persistence of Violence fills that gap in understanding. Colombia is a place that is two countries in one-the ideal and the real-summed up in the idiomatic expression (not unique to Colombia, but particularly popular there) 'Hecha la ley, hecha la trampa' [When you pass a law, you create a loophole]. Less cynically, and more poetically, the Nobel Laureate Gabriel García Márquez deemed Colombians capable of both the most noble acts and the most abject ones, in a world where it seems anyone might do anything, from the beautiful to the horrendous.The Persistence of Violence draws on those contradictions and paradoxes to look at how violence-and resistance to it-characterize Colombian popular culture, from football to soap opera to journalism to tourism to the environment"--